2022
DOI: 10.1155/2022/4084420
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficacy and Safety of Duloxetine and Gabapentin in Diabetic Peripheral Neuropathic Pain: A Meta‐Analysis

Abstract: Background. Diabetic peripheral neuropathic pain (DPNP) is a common chronic pain condition affecting diabetic patients and has growing importance because of the increasing prevalence of patients with type 2 diabetes mellitus. Pain is the most troublesome symptom of DPNP, increasingly recognized as an important and independent feature of DPNP. This meta-analysis aims to compare the efficacy and safety of duloxetine and gabapentin in the treatment of diabetic peripheral neuropathic pain (DPNP) and therefore to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…It is well established that normal wound healing is a controlled anticipated process, and any alteration in the steps of the healing process may result in “venous ulcer,” ‘intractable ulcers or chronic wounds that sometimes become lethal. Hyperglycemic condition hinders the delivery of nutrients and other immunological factors that automatically reflect impaired wound healing (Jiang et al, 2022 ). In diabetic patients, delayed wound healing is related to impaired growth factor production, inflammatory cell function, angiogenesis and fibroblast production and migration (Rose & Kam, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that normal wound healing is a controlled anticipated process, and any alteration in the steps of the healing process may result in “venous ulcer,” ‘intractable ulcers or chronic wounds that sometimes become lethal. Hyperglycemic condition hinders the delivery of nutrients and other immunological factors that automatically reflect impaired wound healing (Jiang et al, 2022 ). In diabetic patients, delayed wound healing is related to impaired growth factor production, inflammatory cell function, angiogenesis and fibroblast production and migration (Rose & Kam, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…The pain is debilitating and adversely affects the quality of life. Moreover, other complications are also attributed to it, including diabetic foot ulcers and diabetic foot deformities [ 12 , 13 ]. DLX is an antidepressant that reduces neuropathic pain by increasing nor-epinephrine and 5-hydroxytryptamine (5-HT) levels in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Duloxetine seems to present proper relief effect on LBP for elder patients, and it can contribute improving pain sensitization. Concerning diabetic peripheral neuropathic pain (DPNP), comparative study was performed for trials on duloxetine versus gabapentin by internet search for related data [31]. From the results of 7 related studies, no significant differences were found for VAS score and overall response rate in both groups.…”
Section: Manuscriptmentioning
confidence: 99%